Association of Epigenetic Differences Screened in a Few Cases of Monozygotic Twins Discordant for Attention-Deficit Hyperactivity Disorder With Brain Structures - Fujisawa, Takashi X.; Nishitani, Shota; Makita, Kai; Yao, Akiko; Takiguchi, Shinichiro; Hamamura, Shoko; Shimada, Koji; Okazawa, Hidehiko; Matsuzaki, Hideo; Tomoda, Akemi (Frontiers in Neuroscience, 2022)
The present study examined the relationship between genome-wide methylation differences and variations in brain structures involved in the development of attention-deficit hyperactivity disorder (ADHD). First, we used monozygotic twins discordant for ADHD to identify candidate DNA methylation sites involved in the development of ADHD. Next, we tried to replicate these candidates in a case-control study. Finally, we examined how methylation rates at those sites relate to the degree of local structural alterations where significant differences were observed between cases and controls. As a result, we identified 61 candidate DNA methylation sites involved in ADHD development in two pairs of discordant monozygotic twins, among which elevated methylation at a site in the SorCS2 gene was replicated in the case-control study. We also observed that the ADHD group had significantly reduced grey matter volume (GMV) in the precentral and posterior orbital gyri compared to the control group and that this volume reduction was positively associated with SorCS2 methylation. Furthermore, the reduced GMV regions in children with ADHD are involved in language processing and emotional control, while SorCS2 methylation is also negatively associated with emotional behavioral problems in children. These results indicate that SorCS2 methylation might mediate a reduced GMV in the precentral and posterior orbital gyri and therefore influence the pathology of children with ADHD.